2022
DOI: 10.1155/2022/6713140
|View full text |Cite|
|
Sign up to set email alerts
|

Study on Health Care Service Standard of Chronic Disease Management Based on Process Reengineering and the Delphi Method

Abstract: The Delphi method is also called an expert consultation method, scientifically measuring the objectivity, practicality, and authority of the metric. This study aims to build a standard plan for chronic disease management care services in hospitals and guide the development of chronic disease management care services. This article proposes a chronic disease management nursing experiment, further revises the current hospital chronic disease management nursing service, redesigns the program, compiles the chronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%